Exploratory Study of Karawang Regency Traditional Food as Culinary Identity - Fernando, Nicky; Rahmanita, Myrza; Wulan, Saptarining (Politeknik Pariwisata NHI Bandung, 2024)
Purpose of the study: This study was conducted to find out the traditional foods in Karwang Regency and find foods that can become the Culinary Identity of Karawang Regency. Design/Methodology: This research uses the explorative qualitative method. with the main data validity test and supporting data source triangulation is used in this research. In this research, the questions asked to several sources that have been determined will be relatively the same and related to the object of research. This is done to ensure that the answers from the interviews between sources are the same. In addition, the material is analyzed and conclusions are drawn from the interview results. Findings: The traditional culinary identity of Karawang Regency includes: jojongkong, green serabi, es walikota, ikan gabus pucung, kue gonjing, bolu kijing, soto tangkar, nasi liwet, kue ali, gegeplak, soto gempol, pepes walahar, kerupuk bontot, gandasturi, kue semprong, dodong hideung and rengginang ketan. Research Limitations/Implications: This study only focused on the Karawang district, West Java. Novelty/Originality of the Study: The results of this study contribute to the Karawang Regency government to find traditional foods that are original and typical of Karawang Regency. In addition, it can be used as a reference in exploring traditional foods in certain areas and finding a culinary identity for the area.